Monitoring procalcitonin in febrile neutropenia: What is its utility for initial diagnosis of infection and reassessment in persistent fever? - Robinson, James; Lamoth, F.; Bally, F.; Knaup, M.; Calandra, T.; Marchetti, O. (2011)
Background: Management of febrile neutropenic episodes (FE) is challenged by lacking microbiological and clinical documentation of infection. We aimed at evaluating the utility of monitoring blood procalcitonin (PCT) in FE for initial diagnosis of infection and reassessment in persistent fever. Methods: PCT kinetics was prospectively monitored in 194 consecutive FE (1771 blood samples): 65 microbiologically documented infections (MDI, 33.5%; 49 due to non-coagulase-negative staphylococci, non-CNS), 68 clinically documented infections (CDI, 35%; 39 deep-seated), and 61 fever of unexplained origin (FUO, 31.5%). Results: At fever onset median PCT was 190 pg/mL (range 30-26'800), without significant difference among MDI, CDI and FUO. PCT peak occurred on day 2 after onset of fever: non-CNS-MDI/deep-seated-CDI (656, 80-86350) vs. FUO (205, 33-771; p<0.001). PCT >500 pg/mL distinguished non-CNS-MDI/deep-seated-CDI from FUO with 56% sensitivity and 90% specificity. PCT was >500 pg/ml in only 10% of FUO (688, 570-771). A PCT peak >500 pg/mL (1196, 524-11950) occurred beyond 3 days of persistent fever in 17/21 (81%) invasive fungal diseases (IFD). This late PCT peak identified IFD with 81% sensitivity and 57% specificity and preceded diagnosis according to EORTC-MSG criteria in 41% of cases. In IFD responding to therapy, median days to PCT <500 pg/mL and defervescence were 5 (1-23) vs. 10 (3-22; p = 0.026), respectively. Conclusion: While procalcitonin is not useful for diagnosis of infection at onset of neutropenic fever, it may help to distinguish a minority of potentially severe infections among FUOs on day 2 after onset of fever. In persistent fever monitoring procalcitonin contributes to early diagnosis and follow-up of invasive mycoses. © 2011 Robinson et al.